Comparing glow discharge plasma and ultrasound treatment for improving aerobic respiration of activated sludge. (1st October 2017) - Van de Moortel, Nina; Van den Broeck, Rob; Degrève, Jan; Dewil, Raf
Abstract: In this paper, a new and innovative technique, glow discharge plasma, is introduced for the treatment of activated sludge, whereby its effect on sludge solubilization, settleability, floc structure and biomass activity for carbon removal and nitrification is investigated. The obtained results are compared to the use of ultrasound for activated sludge treatment, a technique known for its potential to enhancing biomass activity. Results indicate that ultrasound is up to 9 times more efficient in solubilizing activated sludge and disrupting the sludge floc. However, ultrasound has a detrimental effect on sludge settling, even the lowest treatment intensity of 180 kJ/kgMLSS induced a 12% increase in sludge volume index (SVI). Glow discharge plasma on the other hand, improved settleability up to 51%. Glow discharge plasma and ultrasound both positively affect the carbon removal rate. On the long term, extreme conditions even gave rise to a maximum improvement in respiration by 58.6% and 176.5% for a glow discharge plasma and ultrasound treatment. Nitrification, however, was never positively influenced by either of the treatments. Starting from 8297 kJ/kgMLSS for glow discharge plasma and 9000 kJ/kgMLSS for ultrasound, a negative effect on the nitrification rate was found. Graphical abstract: Highlights: GDP was effective in improving the settleability of activated sludge. GDP improved SOURmax of carbon removal up to 24.2% at low SE. US was 4 times more energy efficient for biomass activity improvement. Nitrification was never positively influenced by GDP or US treatment.